Rebel - Tintera, Amy (HarperTeen, 2015)
Having broken free of HARC, seventeen-year-old Wren and Callum escaped north but the Reboot Reservation is preparing to wage all-out war on the humans and the two are torn about their loyalties until Micah commits the ultimate betrayal and their choice is made.